Subjects and objects of operative-cost activity in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article reveals questions about subjects and objects of operational-search activity in the Republic of Kazakhstan, examines legal relations in this area, and suggests new definitions. The author proposes the introduction of a number of changes and additions to the Law of the Republic of Kazakhstan «On Operative-Investigative Activities» on the circle of subjects, issues constituting state or other secrets, and so on.Methodologically, this problem should be solved with the use of methods and techniques in carrying out a difference in the status of subjects and participants in the OIA. From the point of view of the binary-legal aspect, this thesis can be shown by analogy of participants in the constitutional, criminal, civil or administrative process. For example, in a criminal trial, the judge who is considering the case is a party to this process, but since it is legally relevant, it should be considered a subject of criminal proceedings. The same principle should be used to determine the status of other participants in the criminal process: the prosecutor, the lawyer, the victim, the witness, the defendant. Based on the analysis, we note that individuals involved in conducting operational search activities are also subjects of the OIA. Touchingupon the questions about the legal relations that arise in the course of the operational-search functions,we note that to date there is no comprehensive study of this problem.Key words: society, subject, object, legal state, law, search activity, anticorruption, public service,citizen.